Standardized framework for institutional audit for quality in Ghanaian Universities - Oware, Emmanuel Nyarko; Mokoena, Sello (Frontiers in Education, 2025)
This study develops a standardized framework for institutional audits in Ghanaian universities, addressing implementation challenges that compromise audit effectiveness. Through qualitative research, 35 stakeholders across four public and three universities participated in semi-structured interviews, analyzed using thematic analysis grounded in New Institutional Theory. Five themes characterize audit understanding: academic standards alignment, continuous improvement, accountability enhancement, quality assurance alignment, and external recognition. Five implementation challenges emerged: absent standardized frameworks, inadequate preparation, resource constraints, limited improvement implementation, and insufficient stakeholder engagement. Universities demonstrated enhancement capacity through eight improvement measures when supported with clear guidance. Theoretically, the study advances New Institutional Theory in developing countries' higher education by showing how coercive, mimetic, and normative pressures shape institutional audit behavior in resource-constrained contexts. Practically, it provides the Ghana Tertiary Education Commission (GTEC) and African quality assurance agencies with an evidence-based, context-responsive strategic framework that standardizes audit processes while promoting continuous improvement.